Longitudinal flight dynamics and stability of blended wing-body unmanned aerial vehicle with canard as control surface / Rizal Effendy Mohd Nasir - Mohd Nasir, Rizal Effendy (Institute of Graduate Studies, UiTM, 2014)
Blended wing-body (BWB) aircraft concept has its body „blended” with the wing in smooth transition. Unlike conventional aircraft design, BWB aircraft”s body produces lift force and this causes large impact on the flight dynamics and stability. This thesis focuses on flight dynamics of a small unmanned aerial vehicle (UAV) with BWB configuration incorporating a set of canard as longitudinal control surface. The objective is to predict the flight dynamics and stability behaviour of UiTM”s Blended Wing-Body (BWB) unmanned aerial vehicle (UAV) with canard as control surface, known as Baseline- II E-2, in longitudinal mode with classical-approach stability augmentation to achieve level 1 phugoid and short-period modes flying qualities (restricted to damping ratios) as stated in MIL-F-8785C standard. This study proposes simple scheduled feedback gains to the canard. Wind tunnel experiments, computational simulations and empirical estimations were conducted to characterize its aerodynamics and to come up with its aerodynamic mathematical model for flight dynamics derivatives calculation. The flight dynamics model was derived to become Model-N state-space representation and compared to established models. Transient response to a unit step canard input was simulated using these models for flight conditions inside the airplane operating flight envelope (OFE) within its allowed angle of attacks. It was found that the BWB airplane without SAS, despite being statically and dynamically stable, has poor flying qualities for both short-period and phugoid modes.